Diseño y construcción de una prensa electrohidráulica de 20 toneladas para la empresa Acepromet Cia. Ltda. - Criollo Fernández, Rolando Iván (2018)
Acepromet Ltd is a metal-mechanic company specializing in welding and machining process as well as maintenance and repairment of mechanical equipment within which it has faced specific operations, such as, shafts extraction and straighten, and some assembly tasks. Hence the need for installing a hydraulic press in its plant. This new tool will ease all the procedures explained above, which means time and labor saving besides enhancing the quality of the services due to the fact that they were done manually using impact tools which run the risk of causing any accident or giving a defective final service. In this work, a 20-tons hydraulic press was designed and assembled. This capacity is enough for the expected tasks that will be carried out. At the beginning, several existing options were analyzed, so that the designed press fulfils all the company’s requirements regard to functionality and cost. In fact, the proposed design includes materials which are available in the company, such as A-36 steel plates and a hydraulic cylinder in order to decrease the final cost of the press. Next, the hydraulic design is done, including calculations, selection of work elements besides the control and distribution of fluid pressure in the system based on the total tonnage (20 tons). After that, the whole infrastructure which will be subjected to all mechanical stress resulting in the hydraulic system due to the piston is calculated. Afterwards, the structural design is conducted. For this purpose, some available materials owned by the company were used as it was mentioned above. Also, this study has foreseen the possibility that the structure will be enlarged in the case of the hydraulic equipment augments its capacity. Once the hydraulic and structural design were completed, the next step is to assembly the press. Later, this press is going to start up in order to start with its pressure tests. Finally, the obtained results during the pressure tests will be used to de develop a cost-benefit study before to releases the machine to Acepromet Ltd.